Relationships between ethical decision-making and professional behavior in Iranian nursing students - Fatemeh Molaei Tavani; Mozhgan Behshid; Azad Rahmani; Saeid Mousavi; Mehran Seif-Farshad; Parvin Rahmani (Journal of Medical Ethics and History of Medicine, 2022)
Ethical decision-making and professional behavior are essential skills in nursing profession, hence educational programs should be designed to enable future nurses to tackle problems related to ethical decision-making. This descriptive, correlational and analytical study aimed at determining the ability of Iranian nursing students to make ethical decisions as well as relationship between such decisions and professional behavior. The present study used census to select 140 freshmen from the School of Nursing and Midwifery of Tabriz University of Medical Sciences, Tabriz, Iran. Data collection tools included a demographic questionnaire, the Nursing Dilemma Test (NDT) comprising two indices of “nurse’s principled thinking” and “practical consideration”, as well as the Nursing Students Professional Behaviors Scale (NSPBS). The mean scores obtained were 41.3±5.7 for “nurse’s principled thinking”, 21.3±3.7 for “practical consideration”, and 119.07±11.79 for professional behavior. Relationships of professional behavior with “nurse’s principled thinking” and “practical consideration” were insignificant (P>0.05). According to the present study’s findings, nursing students’ weakness in applying ethical concepts to decisions and professional behaviors was due to a gap between scientific material learned and clinical practice. Hence, novel training strategies and programs should be designed to reduce such theory-practice gap